ANALYSIS OF FACTORS AFFECTING POVERTYIN CENTRAL JAVA 2016-2019 - Sumeitri, Atika; Destiningsih, Rian (Transpublika Publisher, 2022)
Poverty is a common issue when discussing economic development. Central Java Province has a fairly high number of poor people and is in the 2nd position on Java Island. This study aims to analyze the effect of average length of schooling, population growth, and human development index on poverty. The data used is panel data obtained from BPS Central Java Province in 2016-2019, the method used is regression analysis of Fixed Effect model panel data with the help of the Eviews 10 application. The results show that the average length of school has a positive and insignificant effect. on poverty, HDI has a negative and significant effect on poverty and economic growth has a negative and insignificant effect on poverty.